Appellatives in the base of microtoponyms (on the example of field names of district of Zielona Góra) - Żuraszek-Ryś, Iwona (Geographical names in physical space, 2016)
The main purpose of research purpose in this article is the analysis of appellatives testified in field names of district of Zielona Góra and specification of the most dominant types among them. The research material comprises 125 common words (derived from 302 toponyms) which were divided into three groups corresponding to the main motivation types, suitable for microtoponyms: appellatives connected with topographic, cultural and possessive motivation. The analysis which was carried out demonstrated that common words which were present in the base of field names of district of Zielona Góra, were usually formations the source of which stems from topographic motivation. The second most frequent words were appellatives connected with cultural motivation. The fewest common words were to be found in adherent motivation. Such preferences in nomination processes referred to microtoponyms are typical of other regions of Poland, too. One has to bear in mind that these processes are determined by territorial and environmental factors.